The Relationship of Knowledge Codification towards Organizational Performance in Indonesian Construction Industry - Theresa Lalita Handaruputri; Budi Hartono (AIBPM Publisher, 2020)
The construction industry, as one of the project-based industries, is still considered as a one-off. Knowledge is often not codified and gone in the next project. Project complexity also brings a more significant challenge to the successful performance of the construction industry. This study examined how codification might affect organizational performance in the construction industry and how project complexity affects their relationship. Findings from 54 construction firms in Indonesia indicated that, as separate independent variables, codification and project complexity brought a positive influence on organizational performance. However, as a moderator variable, project complexity may bring a negative impact on the relationship between codification and organizational performance. There were two clusters formed from cluster analysis, which indicated respondents’ different levels of codification implementation.